Characterization of friction stir welded Al-4Cu-Mg alloy / Al-16Si-4Cu-10SiC composite joint - Hamed Jamshidi Aval; Ivan Galvão (Journal of Advanced Joining Processes, 2024)
This study investigated the tool's rotational speed effect during dissimilar friction stir welding of A390–10 wt.% SiC composite-AA2024 aluminum alloy on microstructure, mechanical properties, and corrosion resistance. The results show that the tunnel defect is created on the advancing side at low rotational speeds of 400 and 600 rpm due to insufficient material flow and a high rotational speed of 1200 rpm due to turbulent material flow in the stir zone. Finely equiaxed recrystallized grains are formed in the stir zone under a high plastic strain rate and particle-stimulated nucleation mechanism. The minimum hardness occurs in the TMAZ of the AA2024 aluminum alloy side, and by increasing the rotational speed from 800 to 1000 rpm, the average hardness in the stir zone decreases from 146.06±8.67 to 137.86±3.98 HV0.1. Also, by increasing the rotational speed from 800 to 1000 rpm, the stir zone's yield strength and ultimate tensile strength decrease by 4.9 and 5.2%, respectively. With the increased rotational speed from 800 to 1000 rpm, corrosion current increases from 0.0213 to 0.0225 mA.cm−2, and corrosion resistance decreases by 17 %. After friction stir welding with a rotational speed of 800 rpm and traverse speed of 20 mm/min, the corrosion resistance of the joint increases and decreases compared to the composite base metal and AA2024 aluminum alloy base metal, respectively.